The Effect of Exclusive Breastfeeding Module Intervention on the Knowledge and Attitudes of Prospective Fathers about Breastfeeding in Bengkulu City - Sabrina Sella; Riska Yanuarti; Agus Ramon; Ida Samidah; Bintang Agustina Pratiwi (Indonesian Journal of Global Health Research, 2025)
Bengkulu City has experienced a decline in exclusive breastfeeding coverage over the past three years (2020-2022). Research related to education for prospective fathers in Bengkulu City has not been widely implemented. This study aims to analyze the effect of exclusive breastfeeding module interventions on the knowledge and attitudes of prospective fathers about breastfeeding in Bengkulu City. A quasi-experimental study was conducted in April-September 2024 with a population of prospective fathers who have wives with a gestational age of more than 27 weeks or the third trimester. The sample consisted of 15 people in the control group and 15 people in the intervention group. The sampling method used purposive sampling. The research variables include the knowledge and attitudes of prospective fathers about breastfeeding, as well as the exclusive breastfeeding module. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis was carried out univariately and bivariately. There were insignificant results from the knowledge variable between the two groups, both pre-test (p = 0.074) and post-test (0.546). While on the attitude variable, significant results were obtained between the two groups, both pre-test (0.001) and post-test (0.044). The exclusive breastfeeding module intervention only affected the attitude variable of prospective fathers about breastfeeding between the intervention group and the control group, both before and after the intervention. While on the knowledge variable of prospective fathers about exclusive breastfeeding, there was no effect between the two groups, both pre-test and post-test.